Disputas pelo monopólio da prática odontológica e a criação da Escola Livre de Odontologia do Pará (1911-1914) - LIMA, Marcelino Carmo de (Universidade Federal do Pará, 2019)
The objective of this research is to analyze the newspapers published in the State of Pará, in the period that preceded the creation, in 1914, of the Escola Livre de Odontologia do Pará, when dentistry was still practiced both by professionals trained in schools located outside the State and by the others. We find that the newspapers, the Estado do Pará and A Província do Pará, in the period before the creation of the Escola that is, from 1911 to 1914 published several news related to the formation and practice of dentistry. What was this news? We found that they expressed, above all, the controversies among the holders of diplomas obtained in schools of dentistry outside the State that sought to exclude the others. The claims about the monopoly of the profession, therefore, as the news shows, began even before the creation of the Escola do Pará.